Microwave Dual Mode Resonator Matched Bandstop Filter - Abdul Halim, Hafrizah Ashidah; Ahmad, Badrul Hisham; Peng Wen, Wong (2010)
This paper discussed the concept and design of dual mode resonator with K–inverter. Theoretical analysis together with the experimental result is presented in this paper. Keyword: Dual mode resonator, matched bandstop filter